PENGARUH E-WOM, CONTENT MARKETING, DAN CONSUMER INNOVATIVENESS TERHADAP MINAT BELI PRODUK SKINCARE DI INDONESIA - Pujinata, Helena Keshya Riconga; Efrata, Tommy Christian (Universitas Ciputra Surabaya, 2023)
This research is done to analyze and to find out the influence of E-WOM, Content Marketing, Consumer Innovativeness on skincare products Purchase Intention in Indonesia. The variables that are used are E-WOM, Content Marketing, Hedonic Innovativeness, Social Innovativeness as independent variables (X) and Purchase Intention as dependent variable (Y). This research uses quantitative research method and data process is done with smartPLS 4.0 version with Structural Equation Modelling (SEM) Partial Least Square (PLS) data analysis method. Sampling is done with non probability sampling method with purposive sampling media by collecting data in the form of questionnaire using linear scale from 1 to 10. Questionnaire is distributed online using Google form media. The population of this research is Indonesian citizenship who are above 17 years old with sample criteria of having social media and attractiveness towards skincare products. Sample of this research is 220 respondents. The result of this research indicates that E-WOM, Content Marketing, Social Innovativeness give positive and significant influence on Purchase Intention of skincare products in Indonesia, whereas Hedonic Innovativeness gives insignificant influence on Purchase Intention of skincare products in Indonesia.